Case Report: Paradoxical Inflammatory Response Syndrome in a Previously Healthy, HIV-Negative, Pediatric Patient With Cryptococcus gatii Meningitis - Cheng, Jessica H.; Cheema, Ritu; Williamson, Peter R.; Dimitriades, Victoria R. (Frontiers in Pediatrics, 2021)
The immunological response of patients with cryptococcal meningitis (CM), particularly those not known to be immunocompromised, has generated an increased interest recently. Although CM is an infection with significant rates of morbidity and mortality, its sequelae may also include a postinfectious inflammatory response syndrome (PIIRS) in patients who have already achieved microbiological control. PIIRS can cause substantial immune-mediated damage to the central nervous system resulting in long-term neurological disability or even death. Steroids have been used successfully in the management of PIIRS in adults. In this report, we present the case of a previously healthy adolescent male with Cryptococcus gattii meningitis who experienced neurological deterioration due to PIIRS after the initiation of antifungal therapy. Immunological workup did not demonstrate any frank underlying immunodeficiencies and genetic primary immunodeficiency screening was unremarkable. He was treated with steroids and recovered clinically; however, intermittent inflammatory episodes needed to be managed through several flares of symptoms. In the setting of the current literature, we discuss the management and monitoring of PIIRS in a pediatric patient, along with considerations of targeted future therapies.